Children's mobility in a failed utopia (Brasília, Brazil). (December 2021) - Müller, Fernanda; Monasterio, Leonardo Monteiro; Dutra, Cristian Pedro Rubini
Highlights: Brasilia's urban planning expected that children would walk to their schools. These days, walking to school is rare in the Federal District. Poor families from peripheries enrol their children in Plano Piloto schools. In our sample, long commuting times are common for these children. Public policies have failed the educational and transportation plans of Brasília. Abstract: This study explores children's mobility and transportation on their routes from home to school and back home in Brasília, the fully planned capital of Brazil. The research is based on Federal District statistical data and workshops conducted with 243 children who attended a government-run elementary school located in the Plano Piloto of Brasília. Results show 15.8% of children below twelve years old of the 229, 073 who attend schools in the Federal District travel to a region far from their local neighbourhoods. 35% of those studying in other regions (22, 485) go to the Plano Piloto. Children's transportation and mobility predominantly among poor elementary school children is highly complex and different from the simple pendulum movement reported in origin–destination surveys. We conclude that the utopia planned for Brasília was not achieved because of the urban structure that banished the poorest people to the periphery, and because of the poor quality of schools in these neighbourhoods. The long daily commute that most children must make is the result of these failures.